Testing the Normality of Residuals of the Modified Gompertz Model used for Modelling the Growth of Callus Cultures from Glycine wightii (Wight & Arn.) Verdc. (Asian Journal of Plant Biology, 2015)
Glycine wightii species is native to Brazil and Africa. It is often known as an important climbing vine-like perennial soybean. It is in the family of Leguminosae, within the sub-family Papilionoideae, under the genus Glycine and with the sun-genus Bracteata. In a prior work, we modeled the growth of the bacterium Glycine wightii from published literatures to acquire crucialgrowth constants. We learned that the modified Gompertz model via nonlinear regression using the least square method was the most effective model to describe the growth curve. Nevertheless, the use of statistical tests to choose the best model relies heavily on the residuals of the curve tobe statistically robust. More often than not, the residuals must be tested for conformation to normal distribution. In order for this assumption to be met, we perform statistical diagnosis tests such as the Kolmogorov-Smirnov, Wilks-Shapiro and D'agostino-Pearson tests.